A Comparative Study on the Effectiveness of Resistance Exercise and Concurrent Exercise Training on Power and Strength of Lower Limbs in Football Players (International Journal of Physiotherapy, 2021)
Background: Football players can sustain repeated muscular effort that requires adequate muscular strength and power and adequately conditioned cardiovascular and respiratory systems. Resistance training improves muscular strength and endurance. Concurrent training involves cardiovascular endurance and resistance training within the same session or closely together within the same day. Concurrent training was promoted as a way promoted to save time while multiple training goals. The study's objective is to compare the effectiveness of resistance exercise and concurrent exercise training on the power and strength of lower limbs in football players.Methods: This was an experimental study design with a convenient sampling method. This was conducted on subjects from the Faculty of physiotherapy, Dr.M.G.R. Educational, and Research Institute and took nearly one month to analyze the study. Based on the inclusion and exclusion criteria, 30 samples were selected and divided into Group A and Group B by convenient sampling method. Group A received Resistance training exercise, and Group B received Concurrent training for two sets of 15 repetitions/twice a week for four weeks. Pre and post-test were measured before and after the study for 1 month, using a vertical jump test. The data were compared and analyzed within and between groups.Result: Comparing the Pre and Post-test scores between Groups (A & B) on maximum Isometric Voluntary Contraction (MIVC) &Vertical Jump Test shows a significant difference in Mean values with P ≤ 0.001.Conclusion: Concurrent exercise training is more effective than resistance exercise on the power and strength of lower limbs.